KONTINUITAS DAN DISKONTINUITAS PERILAKU KORUPSI DI JAWA* - Djoko Dwiyanto (Berkala Arkeologi, 2014)
Corruption has become an inherent behaviour at any event in relationship among one and other parties, both transactionally or collusion and gratification. Both inscriptions and textual evidences in Old Javanese to Modern Javanese showed evidence of abuse of authority and irregularities which led to corruption.Usually, corruption occurs because there are chances and opportunities as well as social structures that encourage corruption. Dependency between the parties need 'protection' (clients) with the ruling party with authority (patron), led to the emergence of provision of services or repayment. Gratification is collusive and often involves various areas of life, both socio-economic and socio-cultural.